Development of Multidisciplinary-Based Indonesian Interactive E-Modules to Improve Students Scientific Writing Competency - Naelofaria, Salmah; Barus, Frinawaty Lestarina; Prasasti, Tri Indah; Siallagan, Lasenna; Siregar, Izuddinsyah (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
Scientific writing is a crucial skill for students to master, as it enables them to become reliable and skilled observers. This study aims to develop an interdisciplinary-based interactive e-module for the Indonesian language course to improve students' scientific writing competence. This learning is conducted in the General Indonesian Language course at universities. The research used the Research and Development (R&D) method with the 4-D model (Define, Design, Develop, Disseminate). The subjects were 55 students from the English Education and English Literature Study Programs at Universitas Negeri Medan. Expert validation results showed a material feasibility of 77.5% and media feasibility of 73.8%, both falling within the feasible category. Student responses reached 81%, which is considered very positive. Furthermore, the average pre-test score increased from 68.2 to 82.7, with an N-Gain of 0.45, placing it in the moderate-high effectiveness category. Based on these discoveries, the developed e-module is considered feasible, practical, and effective for enhancing students’ scientific writing competence.